(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with the artistic comprehension of the man and history concepts in the novel “The Shadows of the Forgotten Park” by Grygoriy Huseynov. This work refers to non-fiction samples of literature, based on documentary facts collected by a local lore writer. This paper focuses on the author’s skill to display the events of the past. The historical era is revealed in the above mentioned work through the recreation of the individual life destiny. The article defines the genre of the investigated work as “a novel in stories”. Each story is a separate, completed story of the person’s fate or a key episode of his life. At the same time, all the stories are built up in a single artistic cycle, reflecting the results of the philosophical comprehension the problem of human being in history. The work is based on reliable, but little-known facts. It contains the gallery of artistic portraits including outstanding persons of Ukrainian history (usually unjustly forgotten, underestimated by their times). The paper also notes about the transformation (degradation) of the person’s moral norms, the loss of spiritual values, caused by the Soviet ideology. Modern times are considered as a certain segment of history, closely connected with the past. It should be noted that, according to the author, the concept of the past / modern times is formal in general. It is sometimes difficult to determine where the past ends, and where the present time starts. They are closely interrelated being in cause-and-effect relation. The modern times are inextricably linked to the mystic. Along with the scenes of the real person’s life in the history there are the characters which are “the shadows” of the past, the mysterious objects (a notebook, a gate) that mark the time and space, moral and ethical oppositions such as the past / modern; spiritual / non-spiritual; happy / disappointed; moral / immoral. The article concludes that the novel “The Shadows of a Forgotten Park” by Grygoriy Huseynov interprets the place, the role of an individual in society and in the world in general through the personal experience of one human life.